Opera in Prison: Impact of an artistic project on the reintegration of young people in prison - Margarido, Cristóvão (2021)
The social intervention through the artistic languages can represent in the life of each subject a great socio-educational significance, contributing to reinforce numerous personal, social, affective, emotional and relational skills. The social reintegration of young prisoners presents a great challenge for professionals, since the period of detention can indeed allow the individual a period of reflection, there are also ties (of friendship, family ...) that fall apart, and that, in most cases, it is important to reconcile. The project "Opera in Prison" searched, through music, theater and dance to promote a strategy of socio-educational intervention that catalyzes a socially framed life. This project, funded by the Calouste Gulbenkian Foundation, took place in the Leiria Prison (youth), having been promoted by Sociedade Artística Musical dos Pousos (SAMP). Since the beginning of 2014, a group of 50 prisoners. To understand the impact of this project on the process of social reintegration of young prisoners, a research methodology was adopted based on interviews with the various stakeholders in the project. The results presented evidenced the role that artistic languages have played in the lives of young prisoners and their families and the way in which they have contributed to a more effective social reintegration.